Raman spectroscopy identified fingernail compositional differences between sexes and age-related changes but not handedness or fingers in a healthy cohort - Nai-Hao Yin; Frances Griffiths; Claire Mann; Helen Dawes; Richard van Arkel; Marwan Bukhari; Jemma G. Kerns (PLoS ONE, 2025)
Background Nail properties and appearances can indicate a person’s underlying systemic diseases. Raman spectroscopy is an established laboratory technique and has been applied to nails, identifying spectral differences between healthy individuals and patient populations. Objective We aim to explore the importance of potential spectral or chemical variations in nails between sexes, age groups, hands, and fingers. Methods Twenty male and twenty female participants without known musculoskeletal or dermatological diseases donated nail clippings from each finger. The clippings were cleaned, and Raman spectra collected and analysed using a standardised protocol. Results In total 2000 spectra were collected. Females have higher intensities of disulphide, protein, and lipid bands, particularly in their 40s, than males. Age-related changes were prominent in female nails, especially in sulphur-related bands. No significant differences were observed between nails from the left and right hands or among different fingers. Limitations We did not control other factors such as diet, medication, or different occupation or sports participation. Conclusion This is the first study to use Raman spectroscopy to compare nail composition across different ages and sexes in healthy adults. The findings provide a strong basis for further studies on nails at the population level for screening or monitoring diseases.